Concentrations of alkaloids, cyanogenic glycosides, polyphenols and saponins in selected medicinal plants from Ecuador and their relationship with acute toxicity against Artemia salina. - Jaramillo-Jaramillo, Carmita; Jaramillo-Espinoza, Anyi; D’Armas, Haydelba; Troccoli, Luis; Rojas de Astudillo, Luisa (Revista de Biología Tropical, 2016)
Alkaloids, polyphenols, cyanogenic glycosides and saponins are among the main chemical compounds synthesized by plants but not considered essential for their basic metabolism. These compounds have different functions in plants, and have been recognized with medicinal and pharmacological properties. In this research, concentrations of the mentioned secondary metabolites were determined in the medicinal plants Artemisia absinthium, Cnidoscolus aconitifolius, Parthenium hysterophorus, Piper carpunya and Taraxacum officinale, from Ecuador, and related with cytotoxic effects against Artemia salina. Alcoholic and aqueous extracts from leaves of these selected plants were prepared at different concentrations. To assess cytotoxicity of these extracts, different bioassays with A. salina were undertaken, and the mortality rates and LC50 were obtained. Besides, concentrations of alkaloids, cyanogenic glycosides, phenols, tannins and saponins were determined by spectrophotometric methods; this constituted the first report of quantification of secondary metabolites in the selected plants from Ecuador. T. officinale had the highest concentration of total phenols (22.30 ± 0.23 mg/g) and tannins (11.70 ± 0.10 mg/g), C. aconitifolius of cyanogenic glycosides (5.02 ± 0.37 µg/g) and P. hysterophorus of saponins (6.12 ± 0.02 mg/g). Tannins values obtained were not adverse to their consumption. Alcoholic and aqueous extracts of selected plants had hemolytic activity depending on the concentration of saponins. Although the values of cyanogenic glycosides were permissible, it was necessary to monitor the presence of this metabolite in plants to minimize health problems. LC50 values ranged from extremely toxic (3.37 µg/mL) to highly toxic (274.34 μg/mL), in P. carpunya and T. officinale, respectively. From correlation analysis, it was observed that increase values of alkaloids concentrations had highly significant (p<0.001) acute toxicity against A. salina, while at a higher polyphenol concentration the level of plants cytotoxicity decreased significantly (p<0.001). The results of principal component analysis showed that saponins apparently were in synergy with polyphenols to decrease cytotoxicity, but antagonize with alkaloids and cyanogenic glycosides, indicating that these secondary metabolites present variability in the mechanisms of action against A. salina, as cytotoxic compounds. These results also demonstrate that polyphenols and saponins can be lethal at low concentrations, demonstrating the potential of brine shrimp bioassay as a model to evaluate plant extracts containing low concentrations of chemical compounds with high polarities. The significant positive correlation between cytotoxicity and concentration of alkaloids confirmed by the bioassay of brine shrimp can be useful to identify promising sources of antitumor compounds, and to evaluate tolerable limits not affecting other benign cells. Contents of secondary metabolites found in the selected plants confer them great pharmacologic values.